Broadband photodetection of MoS2/p-Ge/n-Ge bipolar heterojunction phototransistor - Park, Youngseo; Hwang, Au Jin; Lee, Chanho; Yoo, Geonwook; Heo, Junseok (2021 Conference on Lasers and Electro-Optics, CLEO 2021 - Proceedings, 2021)
MoS2/p-Ge/n-Ge bipolar heterojunction phototransistor is fabricated, which can detect from VIS to NIR. The responsivities are 35.21 and 133.56 A/W at 466 and 1550 nm, respectively. Photocurrent amplification of BHP, 6 times larger than photocurrent of p-Ge/n-Ge and p-Ge/MoS2 photodiodes.
Keywords: 1550 nm; Heterojunction phototransistors; Photo detection; Photocurrent amplification; Responsivity